GuardCare: Child’s Nutritional Status Diagnostics Using Rule-Based Reasoning - Putri, Safira Nabila; Esi Putri Silmina (International Journal of Informatics and Computation, 2025)
Nutritional status is a critical factor in ensuring the proper growth and development of children under five years old. It encompasses both undernutrition (stunting, wasting, and underweight) and overnutrition (obesity). However, existing diagnostic tools are often limited to healthcare facilities, restricting parents' ability to monitor their children’s nutritional health independently. To address this gap, the system was developed using the Mobile Application Development Life Cycle (MADLC) and implements a Rule-Based Reasoning (RBR) engine with forward chaining to diagnose conditions. The results demonstrated high functional stability, with all black box test cases passing successfully. Furthermore, expert validation yielded a feasibility score of 89.09%, categorizing the application as “Very Feasible” and confirming its diagnostic accuracy. This study concludes that the development of the GuardCare application was successful, resulting in a valid and reliable tool for its intended purpose of nutritional status diagnosis.